A new variant of arithmetic mean iterative method for fourth order integro-differential equations solution - Aruchunan, E.; Wu, Yong Hong; Wiwatanapataphee, Benchawan; Jitsangiam, Peerapong (2016)
© 2015 IEEE.In this paper, we introduced a new variant called Modified Arithmetic Mean iterative method (MAM) from standard Arithmetic Mean (AM)iterative method for the solution of fourth order Fredholm Integro-differential equations. The proposed method has been derived with some relevant theories and proof to validate the convergence. In addition, the formulation and implementation of the proposed method in solving some well-posed problems are also presented and investigated based on a number of iterations, CPU time and Root Square Mean Error (RSME). Numerical simulation and comparisons have been carried out and scrutinised with Gauss-Seidel and standard AM iterative methods to validate the effectiveness of the proposed method.